Comparative behaviour of the Anatidae and its evolutionary implications - Johnsgard, Paul A (Wildfowl, 1960)
An attempt has been made to summarize, in broad outline, the variations encountered in the behaviour of the Anatidae, and to relate these variations to their probable evolutionary significance. In particular, variations in manner of pair formation and pair bond length, in geographic distribution and ecology, and the related conditions of allopatry or sympatry with other species are discussed and their probable effects on behaviour are suggested. Instances are mentioned where a knowledge of behaviour would be helpful in judging evolutionary relationships that have thus far eluded taxonomists (e.g., Stictonetta, Heteronetta, Thalassornus), and likewise examples are pointed out where behavioural evidence suggests different relationships from those which are currently accepted (e.g., Lophonetta, Anas, leucophrys, and the eiders).